Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1017/s0022215108002430
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow up after Epley's manoeuvre in patients with benign paroxysmal positional vertigo

Abstract: Epley's manoeuvre remains an effective modality for treatment of benign paroxysmal positional vertigo. A patient age of less than 40 years and duration of attacks of less than three years are good prognostic factors. Exacerbation number and gender do not affect the probability of benign paroxysmal positional vertigo recurrence after five years; however, these factors do affect the duration of time free from the condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
2
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 16 publications
1
15
2
1
Order By: Relevance
“…While Lopez-Escamez and colleagues found recurrence in 10% of patients with PC-BPPV after 1 year of follow-up, Nunez et al reported that the percent recurrence per year was approximately 15%, with approximately 50% having a recurrence by 40 months [10,12]. Rashad described recurrence in 7% of patients after 1 year, and after 5 years this increased to 35% [13]. Sakaida et al found 37% recurrence at 5 years [14].…”
Section: Discussionmentioning
confidence: 98%
“…While Lopez-Escamez and colleagues found recurrence in 10% of patients with PC-BPPV after 1 year of follow-up, Nunez et al reported that the percent recurrence per year was approximately 15%, with approximately 50% having a recurrence by 40 months [10,12]. Rashad described recurrence in 7% of patients after 1 year, and after 5 years this increased to 35% [13]. Sakaida et al found 37% recurrence at 5 years [14].…”
Section: Discussionmentioning
confidence: 98%
“…Out of the 202 patients successfully treated 148 (73.3 %) had 1 procedure and the rest (26.7 %) required 2 procedures. The number of manual CRP treatments necessary to release patients from their condition has previously been reported to be between 2.0 and 2.4 treatments depending on the semi-circular canal affected [39], and another study [33] found that 2.5 manual procedures were required. One included study [21] compared the results of h-CAN treatment with those of h-CUP where 6 patients each required up to 7 treatments and one required 15 treatments.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, the relatively large share of relapses among the TRV chair group and combination therapy group could reflect that the indications for this type of treatment cover the most resilient cases. Indeed, the TRV and combination therapy were overrepresented when it came to CUP that is prone to relapse and difficult to eliminate [21,33]. The symptom duration could also account for some difference in treatment efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…6 Patient age less than 40 years and duration of attacks of vertigo less than 3 years may be a good prognostic factors according to one study. 7 This was not really applicable in our study, as there were only 2 patients below 40 years of age.…”
Section: Discussionmentioning
confidence: 77%